Tafsir Adabi-Ijtima'i di Kawasan al-Gharb al-Islami: Studi Komparasi Tafsir Ibn Badis dan Mohammed Al-Makki Al-Nashiri - Fauzan Adim; Subi Nur Isnaini (Institut Agama Islam Negeri (IAIN) Keiri, 2021)
This paper discusses the interpretation pattern of adabi ijtima>'i in al-Gharb al-Isla>mi’s area by studying the Ibn Badis’s book, Maja>lis al-Tadhki>r and Mohammed al-Makki al-Nashiri’s book, al-Taysi>r fi> Ah>adi>th al-Tafsi>r. This study aims to describe, analyze, and compare the interpretation patterns and tendencies of Ibn Badis and al-Nashiri in their interpretations using historical approach. The results showed that both mufassir carried the same approach in interpreting the Qur'an. They are using the adabi ijtima>'i’s style in their works to improving the social order and solving social problems of their communities. But the difference is Ibn Badis uses his interpretation to counter French colonialism and improve the life of the Algerian Muslim community in general. He called on all parties of his community in Algeria, including the leaders, people, and ulama to unite to continue their struggle against the invaders. Meanwhile, al-Nashiri, even though he lived during the French occupation of Morocco and during the independence of Morocco, but his commentary was written or rather delivered to the public after independence, so that the nuances of the interpretation of adabi ijtima>'i attached to al-Taysi>r fi> Ah>adi>th al-Tafsi>r talked more about improving the bureaucracy, morals and behavior, interaction between people and responding to the phenomenon of society's reality which he considered to be out of the guidance of the Qur'an.